Diagnostic accuracy of magnetic resonance imaging in detecting anterior cruciate ligament injuries (Faculty of Medicine Universitas Indonesia, 2017)
Background: The anterior cruciate ligament (ACL) stabilizes the joint during hyperextension and prevents anterior translation over femur. The objective of this study was to determine the diagnostic accuracy of magnetic resonance imaging (MRI) in detecting ACL injury by taking arthroscopy as gold standard in patients with traumatic knee injury. Methods: Patients fulfilling the study criteria were treated with clinical examination, MRI and then arthroscopy at the Department of Orthopedics and Spine in the Ghurki Trust Teaching Hospital, Lahore. The accuracy, sensitivity and specificity of MRI in diagnosing the anterior cruciate ligament injury were calculated based on arthroscopic findings. All the data were analyzed using SPSS 17.0 version. Results: A total 185 patients were included. 91.1% were males and 8.9% were females with Mean age of 28.25±0.433. The accuracy of MRI in diagnosing the anterior cruciate ligament was 91.89%, with sensitivity of 93.33%, specificity of 85.71%, positive predictive value of 96.55% and the negative predictive value of 75%. Conclusion: MRI is accurate and non-invasive modality for the assessment of ligamentous injuries. It can be used as a first line investigation to patients with suspicion of ACL injury.